Electronically scanned Rotman lens antenna with liquid crystal phase shifters. Issue 7 (1st March 2013) - Christie, S.; Cahill, R.; Mitchell, N.; Munro, Y.; Manabe, A.
Abstract : The performance of a Rotman lens, which forms fixed beams at 0°, ±15° and ±30°, is augmented using liquid crystal phase shifters to simultaneously steer each beam by up to ±7.5°. Measured results are used to demonstrate that the true time delay property of the antenna and voltage controlled phase shifters can be exploited to provide continuously scanned beams with full coverage over an angular range of ±37.5°, and with operation over the band 6–10 GHz.